Development and Validation of Analytical Method for Piperine in Phytopharmaceutical Product Containing Cabe Jawa Fructus by HPLC - Galih, Wening; Permana, Benny; Damayanti, Sophi (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Cabe Jawa fruit (Retrofractii fructus) has empirically known to have effects such as anti-inflammatory and analgesic due to the presence of piperine. The maximum daily dose for piperine is 0.300–0.540 mg/kg/person/day. A reliable analytical method is required to ensure that phytopharmaceutical preparation is safe. This study developed and validated a piperine analysis method using phytopharmaceutical samples containing Cabe Jawa. A Shimadzu prominence HPLC SIL-20A Prominence autosampler and an X-Bridge C18 column (5 m x 250 mm x 4.6 mm) were used in the research devices. The OFAT method optimised the mobile phase, instrument systems, and sample preparation. The instrument system was optimized for acetonitrile:1% glacial acetic acid (48:52), 40°C, and a 1 mL/min flow rate. Each solid and liquid sample was prepared using the multilevel methanol dilution and water-dichloromethane liquid-liquid extraction (LLE) method. The results of validating the analytical procedures for solid and liquid samples were LOD and LOQ of 1.290 g/mL and 4.300 g/mL, 1.310 g/mL and 4 g/mL, respectively. Precision: 0.157% and 1.174%. Accuracy for three different concentrations were 94.232±1.050%, 95.387%±0.176%, and 96.272±1.043%; 88.801±0.428%, 89.473 ±0.252%, and 89.338 ±0.052% respectively. The analysis of the sample's piperine revealed that this method met the criteria for the validation parameters.